Principles and Practices of Food Safety for Vegetable Production in Florida - Amy Simonne (EDIS)
FCS8817, a 7–page fact sheet by Amy Simonne, reviews in detail seven important principles that commercial producers and packers of fresh fruits and vegetables should follow in order to ensure food safety. Includes a list of disease-causing microorganisms of concern and a checklist of potential hazards for producers to use when assessing their operations. Published by the UF Department of Family, Youth and Community Sciences, November 2006.